(3GdeONd Edi Jbhje GddSGf hJYdje GdHjGfs - (3eMeO Hf CMeO Hf gTGe Hf Nda GddNej GdCfOdSj, CHh YHO Gddg,J (B577 (3g` s ((3Ydi Hf eMeO Hf Ydi GdTGQi s)
(3ChdgG (B:s
(3GdMeO ddg bHd cd ebGd hHYO aEf Chd eG jLH Ydi WGdH GddZI JUMjM GdCdaGX GdYQHjI GdeSJYedI GdJi UQaJgG GdYGeI Yf ehVYgG s
(3BNQgG (B:s
(3hbhdge (B: (3CYdeg GdQeGjI cd jhe adeG GSfO eSGYOg QeGfi hgPG GdHjJ ef HjGJ eYf Hf ChS bGdgG ai GHf CNJ dg jbGd dg NHjH fLR GdcJGH HMeO Gddg s
(3QhGjI CHj YHO Gddg eMeO Hf MSh Hf YWjI Yfgs
(3QhGjI Ydi Hf eMeO Hf Ydi Hf eMeO Hf jMji GdZGeV GdeYQha HGHf GdTGQi J SfI (B649 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318s
Keywords: (3GddZIs